Study of Physics Learning in Indoor Games at Transmart Surabaya - Nandi Okta Indriati; Diyah Prasasti Listiantomo; Fika Dina Aprilia; Binar Kurnia Prahani; Dwikoranto (Indonesia Approach Education, 2021)
This study aims to examine the learning of physics in indoor games at Transmart Surabaya. This study uses a qualitative descriptive method, namely by using a documentation study. The target of this research is a modern game that applies the concept of physics contained in the Studio Mini Transmart Surabaya. The method of data collection carried out in this study used the observation method. In this study, it was concluded that some of the games contained in Trans Studio Mini Transmart Rungkut, Surabaya, namely roller coaster games, new york (rotating swing), sky rider, mini electric car, mini train, and bumper car applied several physics concepts. The roller coaster game applies the concept of mechanical energy. In the new york game, the physics concept is applied, namely the concept of rotational motion and harmonic motion. In the game sky rider applies the concept of physics, namely the force of gravity, rotational and circular motion and the moment of inertia. In the mini electric car game, the concept of physics is applied, namely the concept of displacement, velocity, acceleration and friction. In the mini train game, the physics concept is applied, namely acceleration and friction. As well as in the bumper car game applying the concepts of physics, namely acceleration, collision and the law of conservation of momentum.